1995
DOI: 10.1103/physrevb.52.5323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-dynamics simulations of nickel oxide surfaces

Abstract: Molecular-dynamics-simulation techniques have been used to investigate the effect of temperature on the three low index surfaces of nickel oxide. The surface energies for the [100},[110},and Ni [111} surfaces have been calculated as a function of temperature for NiO. The surface energies for all three surfaces were essentially constant up to 2000 K, when surface melting was observed for the less densely packed surfaces such as the [110}and Ni [111}surfaces. The [110}surface reconstructed to give [100} microfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…The formal ion charges Z (Z=+2 for Ni and Z=-2 for O) were used in the Coulomb potential [23,24]. We found that the Fisher's FF model [23] gives slightly better agreement with the experimental Ni K-edge EXAFS signal for c-NiO than the Oliver's one [24], therefore only the former was used in the simulation of nano-NiO.…”
Section: Md-exafs Simulationsmentioning
confidence: 93%
See 4 more Smart Citations
“…The formal ion charges Z (Z=+2 for Ni and Z=-2 for O) were used in the Coulomb potential [23,24]. We found that the Fisher's FF model [23] gives slightly better agreement with the experimental Ni K-edge EXAFS signal for c-NiO than the Oliver's one [24], therefore only the former was used in the simulation of nano-NiO.…”
Section: Md-exafs Simulationsmentioning
confidence: 93%
“…The MD simulations were performed using two FF potential models, developed in the past by Fisher [23] and Oliver [24]. The two models include the same pair interactions, but differ slightly in the numerical values of the FF parameters (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations